Sort of/kind of : réalisations prosodiques - Céline Horgues (Anglophonia)
This paper aims to explore the relationship between prosodic form and the different linguistic functions of the sort of/kind of constructions. Certain previous research has given a simplistic outlook on this relationship, where the prosodic correlates systematically cue the two main types of functions: the nominal use (Type use) is associated with accentual prominence realised with a full form of sort/kind whereas the discourse marker use is realised as non-prominent and phonologically reduced. However, the analysis of a few counter-examples to this generalisation will show that prosody should not be regarded as a simple reflexion of the linguistic function of sort of/kind of but rather as a linguistic marker in its own right contributing to the expression of discourse-specific meanings.